HUBUNGAN STRES AKADEMIK DENGAN KEPRIBADIAN SISWA - Dinny Rahmayanty; Nur Hasanah Harahap Hasanah Harahap; Angelica Angelica; Uswatun Dwi Hasanah; Yodia Setiawati; Zuherni Rahma (Jurnal Bimbingan Penyuluhan Islam, 2023)
Academic stress refers to the pressure that arises when a person faces various stimuli related to the academic field. The impact of existing academic demands produces reactions that include negative thoughts, behaviors, physical states, and feelings. This situation occurs due to internal and external factors that affect individual personality. One aspect of personality that is relevant in this context is hardiness. Hardiness refers to personal attributes that help a person manage and overcome life experiences. Students with a high level of hardiness will become stronger, more resilient, enthusiastic, and able to recover from pressure, so they experience a low level of academic stress. On the other hand, students who lack hardiness tend to feel sad, confused, worried, weak, fragile, and sensitive to pressure, which results in high levels of academic stress. To overcome this problem, the role of parents is very important in providing support and helping to develop a child's personality to make it stronger and more stable.